Deformation sensing of colonoscope on FBG sensor net - Yi Xinhua; Wang Mingjun; Cheng Xiaomin (Institute of Advanced Engineering and Science, 2012)
Owing to the complex condition of human intestinal and non-visualization, Loop formation of colonoscope often happens to hurt the patient during the diagnosis of colon. This paper presents a deformation detecting method using fiber brag grating(FBG) sensor net to real-time display the shape of colonoscope that would help the endoscopist how to manipulate the colonoscope into the body. The structure configuration and packing method of a FBG sensor net was described and the relative coefficient matrix between the curvature and shift of wavelength was acquired by experiment calibration. The position of FGB sensor point on the colonoscope relative to the handling part of the colonoscope can be derived by curvature information and the deformation of colonoscope can be reconstructed using curve fitting. Experiment results verified that the deformation sensing method was feasible and accuracy of the tip position can reach 4.5mm of the colonoscope with the length 1200mm. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1693